TEACHING CHALLENGES IN PANDEMIC TIMES - Daufemback, Valdete; Aparecido Gonçalves, Israel; Prado Atassio, Aline (Revista Gênero e Interdisciplinaridade, 2022)
This paper, promotes an analysis of the practice of teaching in higher education and of changes in relation to the teaching and learning process, through law of the states of Santa Catarina (Brazil) published on March 16 in the Official Gazette of the State and law, nº.343, of March 2020, from the Ministry of Education, which suspended face-to-face classes in favor of exercising academic activities in 2020 remotely. The methodology of this paper is located on the border between the narrative of selected events and the analysis constructed from the experience of changing attitudes and adapting didactic – pedagogical, procedures in the teaching and learning process of the school year, from the classroom to the model remote. It is considered important to reflect and criticize the practices adopted in the area of education by the federal and state governments, in this period of pandemic.